The use of occupation-based interventions and assessments in hand therapy: A cross-sectional survey. - Valdes, Kristin; Naughton, Nancy; Cantero-Téllez, Raquel; Szekeres, Mike (My University, 2021)
Introduction The purpose of this study was to gather information on how hand therapists incorporate occupation-based interventions in their clinical practice and what outcome measures hand therapists use to measure the occupational performance of their clients Study Design Cross-Sectional Survey Design. Methods The 16-item Survey was distributed to members of the American Society of Hand Therapists on two occasions. Results Three hundred eleven hand therapists responded to the survey. Hand therapists use a variety of occupation-based interventions (OBI) in clinical practice and most believe they are important. Findings from this study reveal that incorporating an occupation-based assessment along with or in place of an assessment of body functions and structures is not performed routinely. One hundred twenty-six (41%) respondents indicated that they use occupation-based activities 26-50% of the time with their clients. Discussion The top three OBI interventions used by hand therapists included dressing tasks, cooking and meal preparation, and in hand manipulation of coins and medication. The lack of understanding of the theoretical models regarding occupation-based interventions may be a barrier toward implementation of occupation-based interventions and assessments as many hand therapists may have trained under a medical model. Conclusion Most respondents to this survey indicated that they believe OBI should be performed by hand therapists and use them routinely in practice. The most frequently used type of assessment was the DASH (Disabilities of the Shoulder Arm & Hand). The least frequently used assessment was the Short Form 36 and patient specific occupation-based assessment.
Keywords: Manos - Fisioterapia; Occupation; Hand therapy; Intervention; Assessment